Psychological dynamics of Lengser culture in increasing self-esteem among Sundanese people: A qualitative study - Sihombing , Friza Yovita; Rahmatulloh, Ainurizan Ridho; Wulandari, Nanda Yunika (Universitas Sarjanawiyata Tamansiswa, 2024)
The lengser culture is one of the traditions rich in cultural and spiritual values among the Sundanese community. This tradition not only serves as part of customary ceremonies but also plays a significant role in shaping the identity and self-esteem of individuals within the community. This article aims to explore the psychological dynamics associated with the implementation of the lengser culture and how it contributes to enhancing self-esteem among the Sundanese people. The method used is qualitative research with in-depth interview techniques, involving key informants such as lengser artists, Sundanese cultural leaders, psychologists, and general community members. The results of this study indicate that participation in the lengser culture provides a sense of social attachment, recognition from the community, and a deeper understanding of cultural values, all of which positively contribute to individual self-esteem. Thus, the preservation of the lengser culture is not only important for the continuity of cultural heritage but also for the psychological well-being of the Sundanese community. These findings are expected to encourage further research and policies that support cultural preservation as a tool for improving community quality of life.